Efektivitas Porositas Biofilter Aerob untuk Mendegradasi Parameter Limbah Cair Rumah Makan dengan Menggunakan Micro Bubble Generator - Tuhu Agung Rachmanto; RR. Vira Eryka Kusumaningrum (Prosiding ESEC, 2022)
The restaurant business is growing rapidly in big cities these days, increasing demand for people looking for fast and convenient dining service. Wastewater produced by untreated restaurants can cause increased levels of COD, BOD, TSS, and fatty oils in water bodies. In restaurant wastewater treatment that only uses a grease trap, it required. One of the treatments that can be applied to improve the quality of wastewater from restaurant waste processed by grease trap is by using the aerobic biofilter biological treatment process. Aerobic biofilter is a biological treatment that utilizes media as a place for microorganisms to breed and helps to degrade the pollutant load in restaurant waste in the presence of oxygen supply in the treatment. This research uses an aerobic biofilter with variations in the porosity of the media volume and the best residence time to proceed a continuous system. From this study, the optimal results obtained in thebatch system were COD 88,8%, TDS 79,5%, TSS 85,3% with a residence time of 15 days at a volume porosity of 75% bioball media. The percentage of removal in the continuous system works is stable, namely the removal efficiency of COD 88,6%, TDS 77,6%, and TSS 83,6%.